In vitro 5-LOX and COX inhibitory activity of isolates from Eleusine indica Linn Gaertner (Poaceae) aerial shoots - Jacinto, Adrien Kyle M.​; Torralba, Joanna V.​ (Manila College of Pharmacy, University of the Philippines, 2019)
Goose grass (Eleusine indica) is a locally abundant weed traditionally used as an herbal medicine. Recent studies supported its use in inflammatory processes as evidence by the reduction of LPS-induced inflammation in vitro and in vivo. The aim of this research was to evaluate anti-inflammatory activity of the isolates from E. indica in the context of 5-LOX and COX inhibition. Drugs able to block the two main arachidonic acid pathways is of pharmacological interest due to wide range of anti-inflammatory activity with no ulcerogenic risk.
The anti-inflammatory activity of the samples were tested in vitro using 5-LOX, COX-1, and COX-2 inhibition assays. Additionally, the cytotoxicity of the isolates were evaluated. Lastly, DNA barcoding of the plant; TLC profiling and derivatization of the crude methanol extract and fractions; and characterization of the most active isolate via UPLC-QTOF-MSᴱ were also performed.
Screening of the crude revealed significant dual 5-LOX/COX Inhibition. Analysis of its fractions resulted to increase in the activity for mid polar fractions and decrease in the activity for non-polar and polar fractions. Ethyl acetate fraction, the most active fraction found to be rich in phenolic compounds, were considered tor further study. Further purification afforded nine isolates. Screening of these isolates at SOμg.mL⁻¹ revealed significant reduction in the activity except for isolates 6, 8, and 9 in inhibiting 5-LOX and COX-1. Isolate 6, the most active isolate with moderate hepatotoxic and nephrotoxic profile, were determined to have an IC₅₀ of 16.47μg.mL⁻¹ for 5-LOX, 19.64μg.mL⁻¹ for COX-1 and 22.26μg.mL⁻¹ for COX-2. Two compounds namely Naringenin 7-0-β-D-glucuronide and Tricin-7-O-β-D-glucopyranoside were tentatively identified after mass spectral analysis. These compounds, along with seven other compounds identified from the isolate 6, were responsible for the dual anti-inflammatory activity of the E. indica in vitro.
​Thesis (Master of Science in Pharmacy Major in Pharmaceutical Chemistry)--University of the Philippines, June 2019.
Keywords: Cyclooxygenase 2--Inhibitors.; Grasses; Lipoxygenase; Goosegrass; Wiregrass; Paragis; Eleusine indica Linn Gaertner